Deficit Irrigation Scheduling and Superabsorbent Polymer‐ Hydrogel Enhance Seed Yield, Water Productivity and Economics of Indian Mustard Under Semi‐Arid Ecologies†. (21st January 2019) - Rathore, S.S.; Shekhawat, Kapila; Dass, Anchal; Premi, O.P.; Rathore, B.S.; Singh, V.K.
Abstract: Oilseed brassicas are extensively grown in the water‐stressed ecologies of India. Sufficient irrigation, deficit irrigation scheduling (DIS) with limited irrigation water and rainfed (no irrigation) conditions were assessed with and without the use of superabsorbent polymer‐hydrogel (SAP‐hydrogel) under a micro‐sprinkler irrigation system (MIS) for Indian mustard. Irrigation scheduling at an irrigation water/cumulative pan evaporation ratio (IW/CPE) of 0.8, 0.6 and 0.4, along with use of SAP‐hydrogel, produced almost equal dry matter per plant (113, 115 and 109 g plant −1 ), which was, however, significantly higher ( P  ≤ 0.05) over rainfed (86 g plant −1 ). The seed yield under DIS (0.6 IW/CPE) increased by 39.3% over rainfed + hydrogel (HG). Also, the seed yield obtained under irrigation scheduling at a ratio of 0.4 IW/CPE was found to be similar to that obtained in rainfed + HG treatment. A similar water productivity (WP) of 10 kg ha −1 mm −1 was obtained with DIS at 0.4 IW/CPE + HG and at 0.8 IW/CPE‐HG; however, a higher total water productivity (WPt ) was recorded under DIS at 0.6 and 0.4 IW/CPE + HG (23 and 29 kg ha −1 mm −1, respectively) over the same irrigation schedules excluding HG. The economics of HG application under DIS was better due to higher net returns, although the highest B : C ratio (1.92) was recorded in DIS (0.4 IW/CPE), trailed by irrigation scheduling at IW/CPE 0.8 and 0.6. Overall, it could be concluded that DIS through micro‐sprinkler and use of HG enhanced seed, oil, water productivity and energy dynamics under water‐constrained conditions in semi‐arid ecologies. © 2019 John Wiley & Sons, Ltd. Résumé: Les graines oléagineuses brassicacées sont largement cultivées dans les écologies indiennes soumises à un stress hydrique. Une irrigation suffisante, un calendrier d'irrigation déficitaire (DIS) avec des conditions en eau d'irrigation limitées et pluviales (pas d'irrigation) a été évalué avec et sans utilisation de polymères hydrogels super absorbants (SAP‐hydrogel) dans un système d'irrigation par micro‐aspersion (MIS) pour la moutarde indienne. La planification de l'irrigation suivant le rapport eau d'irrigation/bac d'évaporation cumulatif (IW/CPE) 0.8, 0.6 et 0.4, ainsi que l'utilisation de SAP‐hydrogel ont produit une matière sèche presque égale par plante (113, 115 et 109 g plante −1 ), cependant, significativement plus élevé ( P  ≤ 0.05) que l'agriculture pluviale (86 g plante −1 ). Le rendement en graines sous DIS (0.6 IW/CPE) a augmenté de 39.3% par rapport à celui des cultures pluviales + hydrogel (HG). En outre, le rendement en semences obtenu dans le cadre d'un programme d'irrigation à un ratio de 0.4 IW/CPE était similaire au rendement en graines obtenu dans le traitement pluvial + HG. Une productivité de l'eau similaire (WP) de 10 kg ha −1 mm −1 a été obtenue avec le DIS à 0.4 IW/CPE + HG et à 0, 8 IW/CPE‐HG, cependant une productivité totale en eau (WPt ) supérieure a été enregistrée sous DIS à 0.6 et 0.4 IW/CPE + HG (23 et 29 kg ha −1 mm −1, respectivement) sur les mêmes calendriers d'irrigation sans HG. L'économie de l'application de HG sous DIS était meilleure en raison de rendements nets plus élevés, bien que le ratio B : C le plus élevé (1.92) ait été enregistré dans le DIS (0.4 IW/CPE), consécutif à un calendrier d'irrigation à IW/CPE de 0.8 et 0.6. Dans l'ensemble, on peut conclure que le DIS par micro‐aspersion et l'utilisation de HG améliorent la productivité des semences, la consommation de pétrole, la productivité de l'eau et la dynamique énergétique dans des conditions de pénurie d'eau dans les écologies semi‐arides. © 2019 John Wiley & Sons, Ltd.